Employee Payment Data Application Design: Case Study in Cv. Twins19 - Noviyanti Islami; Dadang Latif; Ikbal Jamaludin; Nanang Suciyono; Rizal Parghani; Susanto Susanto (Informatics Management, Engineering and Information System Journal, 2023)
At first, employees collect attendance support letters containing attendance sheets and permits if not working as well as overtime certificates to the financial administration section, after which the financial administration will calculate salaries first to be submitted to the accounting department. Because employee payroll is still done manually, errors often occur in absenteeism and in calculating salaries given to employees. Then the frequent occurrence of errors in recording reports is also because the payroll is still done manually. This system is analyzed and designed using descriptive research methods and development techniques using the waterfall method. The programming language used by this system is PHP with XAMPP web server and PHPMyAdmin database. This employee payroll application that has been created can help companies make it easier to record payroll transactions, and archive payroll and attendance reports.